SUATU TINJAUAN TUGAS DAN FUNGSI PAMONG PRAJA DALAM MENEGAKKAN PERATURAN DAERAH DI KABUPATEN KUBAR - Yonathan Gun (Journal of Law ( Jurnal Ilmu Hukum ), 2014)
Abstract Indonesian state in managing and organizing the system of government must have ideals to be achieved, the ideals and objectives is kritilisasi values are believed to be the truth by people who later used as the foundation in carrying out development dinegarannya. Similarly, the Indonesian state has a goal like that on the opening goal as stated in the preamble of the Constitution 45, particularly in the fourth paragraph to protect all the people of Indonesia and the entire country of Indonesia, promote the general welfare, the intellectual life of the nation and participate implement order and world peace based on freedom, abiding peace and social justice.Definition of Municipal Police under Act No. 32 of 2004 on Regional Government is the head of the area assigned to assist the region in order to hold public peace and order as well as organizing public peace and order and enforce the Regulation (Article 148 paragraph (1) of the Act No. 2 of 2004 on Regional Government).